2017
DOI: 10.1074/jbc.m116.753822
|View full text |Cite
|
Sign up to set email alerts
|

Absence of miR-146a in Podocytes Increases Risk of Diabetic Glomerulopathy via Up-regulation of ErbB4 and Notch-1

Abstract: Edited by Xiao-Fan WangPodocyte injury is an early event in diabetic kidney disease and is a hallmark of glomerulopathy. MicroRNA-146a (miR146a) is highly expressed in many cell types under homeostatic conditions, and plays an important anti-inflammatory role in myeloid cells. However, its role in podocytes is unclear. Here, we show that miR-146a expression levels decrease in the glomeruli of patients with type 2 diabetes (T2D), which correlates with increased albuminuria and glomerular damage. miR-146a levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 83 publications
(101 reference statements)
3
76
1
Order By: Relevance
“…71,74 The complexities of the roles of miR-146a under diabetic conditions are also reflected in studies of diabetic nephropathy (DN). Similar to the report by Feng et al, 72 Lee et al 75 showed that miR-146a expression was decreased in the glomeruli of T2D patients and of a T2D mouse model, BTBR ob/ob mice. However, several other groups reported opposite observations.…”
Section: Mir-146 Inhibits Diabetes-induced Retinal Defectsupporting
confidence: 76%
See 1 more Smart Citation
“…71,74 The complexities of the roles of miR-146a under diabetic conditions are also reflected in studies of diabetic nephropathy (DN). Similar to the report by Feng et al, 72 Lee et al 75 showed that miR-146a expression was decreased in the glomeruli of T2D patients and of a T2D mouse model, BTBR ob/ob mice. However, several other groups reported opposite observations.…”
Section: Mir-146 Inhibits Diabetes-induced Retinal Defectsupporting
confidence: 76%
“…In spite of the differences of its expression levels at different stages of diabetes in different tissues of different species, the consensus message from numerous studies is that miR-146a is protective against diabetes-induced damages, however, through different mechanisms. In retina, miR-146a protects by inhibiting diabetes-induced increased expression of fibronectin 72 and NF-jB activation and subsequent inflammatory responses 36 ; while in the kidney, it limits diabetes-induced increased expression of Notch-1 and Ergb4 and their downstream events, 75 besides fibronectin. 72 Additional independent, well-controlled, longitudinal tissue-specific studies are warranted to fully uncover the roles of miR-146a in DR and other diabetic complications, and its potential as a therapeutic target for the treatment of DR and other ocular diseases.…”
Section: Mir-146 Inhibitsmentioning
confidence: 99%
“…Blocking ErbB4 with a known antagonist, erlotinib, protected animals from the development of albuminuria and significantly reduced glomerular damage, suggesting a role for EGFR cell signaling in DKD. 61 Recently, the beneficial effect of erlotinib and the role of EGFR signaling in glomerular crescent formation have been also shown by Tharaux and colleagues. 62 To further unravel the consequences of activated EGFR signaling, Tharaux took a closer look at Stat3, which increases in many glomerular diseases, with explicit attention to miRNA-92a, a known downstream target of Stat3 (P.L.…”
Section: The Role Of Micrornas In the Podocytesmentioning
confidence: 88%
“…In an attempt to explain why diverse courses of disease occur among patients with diabetic kidney disease (DKD), Gupta and colleagues 61 found differential expression of miR-146a, which is known to be involved in immune system regulation. In humans, reduction of miR-146a expression was correlated with disease progression and high-grade proteinuria.…”
Section: The Role Of Micrornas In the Podocytesmentioning
confidence: 99%
“…Recently, a study revealed a central role for miR‐146a in the initiation and progression of melanoma by regulating Notch signaling . Previous studies have suggested that miR‐146a protects against diabetic glomerulopathy and podocyte injury by directly targeting notch receptor 1 ( Notch1 ) and erb‐b2 receptor tyrosine kinase 4 ( ErbB4 ) . miR‐146a is sufficient to protect joint cartilage from degeneration through inhibiting the feedback loop of Notch 1/interleukin (IL)‐6 during aging or trauma .…”
mentioning
confidence: 99%